2013
DOI: 10.5012/bkcs.2013.34.3.773
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 1-D BiSI and 2-D BiOI Nanostructures

Abstract: We have prepared 1-D BiSI and 2-D BiOI nanostructures, and characterized them by scanning electron microscopy, transmission electron microscopy (TEM), X-ray diffraction crystallography, thermogravimetric analysis/differential scanning calorimetry, and UV-visible absorption. Here, we first report clear HR-TEM image of BiSI. In addition, we first found that the growth direction of BiSI is [12-1] plane, with the neighboring distance of 0.30 nm. The crystal structures of BiSI and BiOI are found to be orthorhombic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the case of chemical vapor deposition, it is also noteworthy that the stoichiometry of BiSI is seldom attainable due to the incongruent evaporation of the crystalline compound, forming the corresponding halide . While hydrothermal or solvothermal , methods have been reported for BiSI nanocrystals and are much simpler, they are not without their drawbacks. When the starting materials are salts of the participating elements such as nitrates or chlorides for bismuth, thiourea or sulfides for sulfur, and iodide salts for iodine, the product often presents BiOI or Bi 19 S 27 I 3 as secondary phases, ,, thus hindering the creation of a pure product.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of chemical vapor deposition, it is also noteworthy that the stoichiometry of BiSI is seldom attainable due to the incongruent evaporation of the crystalline compound, forming the corresponding halide . While hydrothermal or solvothermal , methods have been reported for BiSI nanocrystals and are much simpler, they are not without their drawbacks. When the starting materials are salts of the participating elements such as nitrates or chlorides for bismuth, thiourea or sulfides for sulfur, and iodide salts for iodine, the product often presents BiOI or Bi 19 S 27 I 3 as secondary phases, ,, thus hindering the creation of a pure product.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of techniques have been employed for preparation of BiSI, such as the Bridgman–Stockbarger technique, vapor–phase growth, spray pyrolysis, flux reaction, gel process, mechanochemical route, and hydrothermal , and solvothermal methods. , Mostly, the synthesized BiSI crystals had a 1D morphology. However, to the best of our knowledge, 1D nanostructure arrays of BiSI have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…60 Moreover, Ganose et al have demonstrated the suitability of BiSI for photovoltaic application through theoretical calculations, and predicted a spectroscopically limited maximum efficiency of 22.5% for BiSI. 61,62 So far, a number of techniques have been employed for preparation of BiSI, such as the Bridgman−Stockbarger technique, 52 vapor−phase growth, 63 spray pyrolysis, 64 flux reaction, 65 gel process, 66 mechanochemical route, 67 and hydrothermal 49,68 and solvothermal methods. 55,69−71 Mostly, the synthesized BiSI crystals had a 1D morphology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Single crystals of bismuth sulphoiodide (BiSI), a chalcohalide with 1D crystallographic dimensionality, 34 have been fabricated by hydrothermal, solvothermal, Bridgman-Stockbarger, and vapor growth methods. 51,[57][58][59][60] Indirect bandgaps of 1.55-1.61 eV have been reported for the rod-like crystals which are more suitable for single-junction solar cells than the wider bandgap (CH 3 NH 3 ) 3 Bi 2 I 9 . 57 BiSI has been assigned to the Pnam space group through X-ray diffraction studies, with the structure consisting of covalently bonded ([BiSI] ∞ ) 2 ribbons held together by van der Waals interactions between the ribbons.…”
Section: A Single Crystalsmentioning
confidence: 99%
“…51,[57][58][59][60] Indirect bandgaps of 1.55-1.61 eV have been reported for the rod-like crystals which are more suitable for single-junction solar cells than the wider bandgap (CH 3 NH 3 ) 3 Bi 2 I 9 . 57 BiSI has been assigned to the Pnam space group through X-ray diffraction studies, with the structure consisting of covalently bonded ([BiSI] ∞ ) 2 ribbons held together by van der Waals interactions between the ribbons. 33,34 Density functional theory (DFT) calculations predict anisotropic conductivity, with higher mobility along the ribbons (covalent bonds) than between them (weaker van der Waals interactions), suggesting controlled vertical growth of BiSI is key for good charge transport in devices.…”
Section: A Single Crystalsmentioning
confidence: 99%